Increased GABA Levels in Medial Prefrontal Cortex of Young Adults with Narcolepsy - Kim, Seog Ju (Associated Professional Sleep Societies, LLC, 2008)
STUDY OBJECTIVES: To explore absolute concentrations of brain metabolites including gamma amino-butyric acid (GABA) in the medial prefrontal cortex and basal ganglia of young adults with narcolepsy. DESIGN: Proton magnetic resonance (MR) spectroscopy centered on the medial prefrontal cortex and the basal ganglia was acquired. The absolute concentrations of brain metabolites including GABA and glutamate were assessed and compared between narcoleptic patients and healthy comparison subjects. SETTING: Sleep and Chronobiology Center at Seoul National University Hospital; A high strength 3.0 Tesla MR scanner in the Department of Radiology at Seoul National University Hospital. PATIENTS OR PARTICIPANTS: Seventeen young adults with a sole diagnosis of HLA DQB(1) 0602 positive narcolepsy with cataplexy (25.1 ± 4.6 years old) and 17 healthy comparison subjects (26.8 ± 4.8 years old). INTERVENTIONS: N/A. MEASUREMENTS AND RESULTS: Relative to comparison subjects, narcoleptic patients had higher GABA concentration in the medial prefrontal cortex (t = 4.10, P <0.001). Narcoleptic patients with nocturnal sleep disturbance had higher GABA concentration in the medial prefrontal cortex than those without nocturnal sleep disturbance (t = 2.45, P= 0.03), but had lower GABA concentration than comparison subjects (t = 2.30, P = 0.03). CONCLUSIONS: The current study reports that young adults with narcolepsy had a higher GABA concentration in the medial prefrontal cortex, which was more prominent in patients without nocturnal sleep disturbance. Our findings suggest that the medial prefrontal GABA level may be increased in narcolepsy, and the increased medial prefrontal GABA might be a compensatory mechanism to reduce nocturnal sleep disturbances in narcolepsy. CITATION: Kim SJ; Lyoo IK; Lee YS; Sung YH; Kim HJ; Kim JH; Kim KH; Jeong DU. Increased GABA levels in medial prefrontal cortex of young adults with narcolepsy. SLEEP 2008;31(3):342-347.